Evaluation Implementation of the Independent Curriculum for Physical Education Learning and Sport Health - Irfan; Ramli; Bachtiar, Ishak; Cayati (Universitas Pendidikan Ganesha, 2024)
This research is motivated by the problem of the quality of PJOK learning processes and outcomes that have yet to reach the expected standards. This problem can potentially hamper the effectiveness of curriculum implementation in improving student competencies. This research aims to analyze objective information and find improvements in the quality of the process and output in PJOK learning. This type of research is evaluative with descriptive research design. The subjects of this research trial involved 85 students from grades 7 and 8 who participated in PJOK learning. Data was collected through interviews, observations, questionnaires, and document studies with instruments tested for validity and reliability. The data analysis method used is quantitative and qualitative descriptive analysis. The results showed that the quality of the PJOK learning process was in a suitable category, while the quality of the learning output was classified as very good. The conclusion of this study shows that although the quality of PJOK learning is adequate, some aspects still require improvement to ensure more optimal effectiveness in achieving student competence. This research implies the need to strengthen teacher competence in designing and implementing curriculum-based learning to improve the overall quality of learning.